A study of foreign intervention within different geopolitical spheres aimed at addressing ethnic conflict on the intra-state level - Aldrich, Theuns Christof (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1999.